2015
DOI: 10.1007/978-3-319-03119-4_11
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Oil Recovery Techniques for Indian Reservoirs

Abstract: The overall oil production worldwide has declined due to the increase in maturity of the oil reservoirs. In developing countries like India, the oil production and demand plays a crucial role for the development of economy of the country. However, the domestic crude oil production is insufficient to meet the requirement for energy. Thus, there is a big challenge to minimize the gap between the demand and supply for crude oil. Several methods to enhance oil recovery have been developed to increase the productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 78 publications
(84 reference statements)
0
8
0
Order By: Relevance
“…In the case of microbial methods, microorganisms help to degrade longchain hydrocarbons into short-chain hydrocarbons, thereby reducing the viscosity and increasing the mobility of the HCO. 12 Steam flooding is the most frequently used thermal method for the reduction of viscosity of heavy crude oil. The injection of heat breaks down the asphaltene molecules, thereby causing a reduction of the viscosity and further enabling the crude oil to flow toward the production well.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of microbial methods, microorganisms help to degrade longchain hydrocarbons into short-chain hydrocarbons, thereby reducing the viscosity and increasing the mobility of the HCO. 12 Steam flooding is the most frequently used thermal method for the reduction of viscosity of heavy crude oil. The injection of heat breaks down the asphaltene molecules, thereby causing a reduction of the viscosity and further enabling the crude oil to flow toward the production well.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the cell surface hydrophobicity (CSH) of P. uorescens was higher when grown on eicosane, while the CSH of P. aeruginosa was higher with the hexadecane substrate. 22 Hence, we can infer that the growth of P. aeruginosa was found to be higher in the presence of hexadecane, whereas the growth of P. uorescens was higher in the presence of eicosane.…”
Section: Growth Of the Microorganisms On Paraffinsmentioning
confidence: 83%
“…In our previous work, 22 we have executed the studies regarding the production of biosurfactants using Pseudomonas aeruginosa and Pseudomonas uorescens in the presence of various long chain hydrocarbons, such as hexadecane and eicosane. The above-mentioned study has presented the improvement in the production of biosurfactants using these two bacteria in the presence of hydrocarbons, their characterization, stability, and interaction with solid and liquid paraf-ns.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the EOR processes have an increased recovery to about 30-40% or more of the original oil in place (OOIP) as compared with just 15-40% recovery through primary and secondary methods (Sakthipriya et al 2015). Because of microscopic and macroscopic factors, about 60% of crude oil (OOIP) is left unswept in the reservoirs.…”
Section: Unswept Oil In the Low Permeable Reservoir Zonesmentioning
confidence: 99%